Establishment of surface plasmon resonance chip-based viral assay for pseudorabies virus infection - Honari, Parisa (2011)
Studies were conducted to establish a viral based biochip using Surface Plasmon Resonance (SPR) technology for detection of Pseudorabies virus (PrV. To establish such biochip, series of optimizations were carried out. Different Ligands including P-PrV, PrV/PAb, PrV/gC-mAb and Vero cells were immobilized on the surface of the selected appropriate carboxylated chips. The optimum conditions of immobilization and the level of immobilization achievement were different based on the molecular biochemistry of each ligand. Higher immobilization level belonged to PrV/PAb (13560 RU) and the lowest immobilization level to Vero cells (514 RU). A Regeneration scheme was obtained for P-PrV, PrV/gC-mAb, PrV/PAb and Vero cells each associating with specific analyte. Additionally, a nonenveloped virus, Infectious Bursal Disease Virus (IBDV), an enveloped virus , Classical Swine Fever Virus (CSFV), and a non-viral biomolecule, insulin, were adopted in this regeneration scheme for comparison purposes. The results of regeneration showed when an enveloped virus as one of the interacting partners was considered, acidic solution or a combination of acidic and chelating solution were the most effective regeneration solutions. Whilst, a combination of basic and chelating solution was found to be the most effective regeneration solution when a non–enveloped virus (IBDV) was one of the interactant partners. Thus, the optimum regeneration conditions were dependent on the nature of analyte-ligand bond. Prior to application of established chip in antiviral and mutant assays, the chip was validated in terms of specificity. The chip immobilized with PrV/gC-mAb was found to be specifically sensitive to P-PrV with the highest interaction of ~582 RU. Also, the sensitivity of this chip with limit of detection (LOD) of 1.5 PFU enabled the early detection of virion in supernatants collected from cell culture even prior to formation of cytopathic effect (CPE). Following the validation of biochip, several viral assays for detection of virus in crude samples, screening of virus-antibody interactions, antiviral investigation and detection of mutant virus (BUDR7-PrV) were designed using bovine lactoferrin (BLf) as the investigated antiviral. The potential inhibitory effect of BLf as an antiviral against PrV was revealed through both conventional cell based method and SPR chip based method. BLf with the concentrations of 15 mg/mL and 10 mg/mL was able to significantly reduce the plaque size up to 34.37% and 27.84%, respectively. Besides, the number of plaques was significantly reduced to 13.35% and 9.47% in the presence of BLf with the concentrations of 15 mg/mL and 10 mg/mL, respectively. Accordingly, the results obtained from SPR analysis confirmed BLf inhibitory effect. Based on the SPR analysis, RU was reduced 18.32% when using 15 mg/mL of BLf, while 10.13% reduction of RU was obtained when using 10 mg/mL of BLf. Mutant detection was successfully conducted via established SPR chip. Conventional Polymerase Chain Reaction (PCR) and Western Blot (WB) analyses were employed to investigate the existence of gC gene and its protein. The comparison of SPR based assays and WB revealed that SPR assay is fast, reliable, label free, automated and yet required lower (lesser 10 folds) amount of samples. In conclusion, this study has successfully established an optimized SPR protocol for chip based viral assays specifically with the advantage of early virus detection.